15 Cardiac magnetic resonance (CMR) assessment of right ventricular-pulmonary arterial coupling and right ventricular trabecular complexity: impact on prognosis in patients undergoing lung transplant assessment. (March 2019) - Sarri, G; Halim, K; Mccurry, M; Pierce, I; Rahman-Haley, S; Yesudass, A; Joseph, M; Simon, A; Carby, M; Reed, A; Wong, J
Abstract : Introduction: Right ventricular (RV) function strongly influences prognosis in pulmonary hypertension (PH), but it remains unclear what key metrics are most clinically relevant. The purpose of this study was to assess the clinical relevance of both RV trabecular complexity and adequacy of RV functional adaptation to increased afterload as assessed by CMR in patients undergoing lung transplant assessment. Methods: Between 2013 and 2018, 84 consecutive patients underwent lung transplant assessment with echocardiography and CMR (1.5T - Siemens Aera) to assess biventricular volumes and function as well as late gadolinium enhancement (LGE). RV trabecular complexity was assessed by its fractal dimension (FD) on CMR, using freely available code (FracAnalyse). RV functional adaptation to increased afterload was assessed with the RV-pulmonary arterial (PA) coupling index (stroke volume(SV)/end-systolic volume(ESV) ratio). Survival was analyzed using the Cox proportional hazard ratio with the primary outcome of time to death. Results: In total 84 patients (median age 53±16 years, 54% male) were included in analysis. Median follow up period was 19.3±17.2 months. Underlying lung disease was recorded in 98% of the study population. Tricuspid regurgitation was echo-detected in 66 patients; 77% (51pts) had echo-calculated pulmonary hypertension (PH) with an estimated RV systolic pressure >35 mmHg and estimated mean PA pressure of 30±10 mmHg. 78.4%, 15.7%, and 5.9% of PH patients were categorized to Groups 3, 5 and 1 of WHO PH classification respectively. Mean LV and RV ejection fraction were 62%±1.07% and 51%±18% respectively. Both SV/ESV and RV FD correlated to mPAP, CMR-derived right atrial area, RVEDVi and RVESVi (table 1 ). RV FD did not differ significantly in patients with PH. Survival was predicted by SV/ESV ratio, RVEF, indexed RV end-diastolic volume (EDVi), RV end-systolic volume (ESVi), and mPAP on univariate analysis (table 1 ; SV/ESV carried a hazard ratio of 0.12, p<0.005). Conclusions: In patients with underlying lung disease referred for lung transplant assessment, RV functional adaptation to afterload assessed by CMR seems to predict survival. Fractal analysis of RV trabecular complexity correlated with metrics influencing RV remodelling and contractility, although not survival. Assessment in a larger cohort is required to determine utility of these metrics.